Reproductive Biology Of The Sumatran Rhinoceros (Dicerorhinus Sumatrensis) In Captivity - Zainuddin, Zainal Zahari (1995)

(untitled)
At Zoo Melaka, and the Sumatran Rhinoceros Breeding Centre in Sungai Dusun, seven wild-caught females, three wild-caught males and one captive born female Sumatran rhinoceros (Dicerorhinus sumatrensis) were studied from 1990 and 1994 to obtain information which could assist in the captive breeding of this endangered animal. The anatomy of the reproductive system was based on two post mortem specimens and transrectal real-time ultrasonography in six adult females. The cervix consisted of several folds, the uterus was bicornuate with a short body and prominent horns, and the ovaries were completely covered by the fimbriated end of the fallopian tube. The internal genitalia could be imaged by ultrasonography. The testes were located within a pendulous scrotum. Two lateral projections were located at the base or the penis A well-defined processes glandis was present at the tip of the penis. The accessory glands and the testes could be imaged by ultrasonography. The average length of the oestrous cycle as measured by plasma progesterone levels using the radioimmunoassay technique was 21 days. Oestrus determined by receptivity towards the male was about 24 hours. Common signs of oestrus were: increase frequency of urine spraying, tail raising or tail swinging, anogenital and other contacts. Mounting was recorded but the inability of the male to achieve intromission was probably the reason for failure of females to conceive. Six ejaculates were collected from a male, 4 to 6 years of age, by a combination of penile massage and an artificial vagina. The volume of semen was about 25 ml and the concentration was about one million spermatozoa/ml. It is concluded that ultrasonography, semen analysis and hormonal assays could provide valuable information for successful breeding of the S umatran rhinoceros in captivity. Because of the aggressive behaviour of the male, testing females for sexual receptivity with a male should be replaced by ultrasonography and progesterone measurements for the prediction of oestrus. The recruitment of additional males for breeding is urgently needed. Improvements in semen collection and cryopreservation are needed for future use of artificial insemination if natural mating is not possible or fails.